Variable separation method for solving boundary value problems of isotropic linearly viscoelastic bodies; Acta Mechanica; Vol. 231, iss. 9 - Svetashkov A. A. Aleksandr Andreevich; Kupriyanov N. A. Nikolay Amvrosievich; Pavlov M. S. Mikhail Sergeevich; Vakurov A. A. Andrey Aleksandrovich (Original paper, 2020)
Title screen